Re-presenting feminist methodologies :nterdisciplinary explorations - Kalpana Kannabirān, Ed; Padmini Swaminathan,Ed (Routledge, 2019)
This book tracks the trajectory of gender in the social sciences and humanities through an exploration of the challenges and contradictions that confront contemporary feminist analysis as well as future directions. Drawing on research in India, the essays in the volume engage with the subject in imaginative ways, each one going beyond documenting the persistence of gender inequality, instead raising new questions and dilemmas while unravelling the complexities of the terrain. They also interrogate extant knowledge that has 'constructed' women as 'agentless' over the years, incapable of contesting or transforming social orders - by taking a close look at gendered decision-making processes and outcomes, sex for pleasure, health care practices, content and context of formal schooling or the developmental state that 'mainstreams' gender. Do existing feminist methodologies enable the understanding of emerging themes as online sexual politics, transnational surrogacy or masculinist 'anti-feminist' sensibilities? The feminist methodologies delineated here will provide readers with a toolkit to assess the criticality of gender as well as its nuances. The work foregrounds the importance of intersectionality and builds a case for context-specific articulations of gender and societies that destabilize binary universals. This volume will be useful to scholars and researchers across the disciplines of the social sciences and humanities, especially gender studies, women's studies, feminism, research methodology, education, sociology, political science and public policy.